2019
DOI: 10.1007/s13361-019-02174-x
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Types of Lipids Amenable to Native Mass Spectrometry of Lipoprotein Complexes

Abstract: Native mass spectrometry (MS) has become an important tool for the analysis of membrane proteins. Although detergent micelles are the most commonly used method for solubilizing membrane proteins for native MS, nanoscale lipoprotein complexes such as nanodiscs are emerging as a promising complementary approach because they solubilize membrane proteins in a lipid bilayer environment. However, prior native MS studies of intact nanodiscs have employed only a limited set of phospholipids that are similar in mass. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 46 publications
0
52
0
Order By: Relevance
“…Like POPC/SOPE and DPPC/SOPE nanodiscs, at higher collision voltages, SOPE is preferentially ejected from DPPG/SOPE nanodiscs in positive ionization mode. In contrast to pure PG nanodiscs that split in half at higher collision voltages in positive mode, 24,42 DPPG/SOPE nanodiscs continually lose lipids that carry charge as the collision voltage increases but retain two MSP belts.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Like POPC/SOPE and DPPC/SOPE nanodiscs, at higher collision voltages, SOPE is preferentially ejected from DPPG/SOPE nanodiscs in positive ionization mode. In contrast to pure PG nanodiscs that split in half at higher collision voltages in positive mode, 24,42 DPPG/SOPE nanodiscs continually lose lipids that carry charge as the collision voltage increases but retain two MSP belts.…”
Section: Resultsmentioning
confidence: 93%
“…Native mass spectra were analyzed using UniDec and MetaUniDec software as previously described. 12,24,[29][30] The mass range was set from 20-250 kDa with a charge range of 5-25. The peak width was set to 5 m/z.…”
Section: Introductionmentioning
confidence: 99%
“…However, the monodispersity and homogeneity of nanodiscs allows them to be analyzed by nMS without collisional activation, which better preserves native interactions. Marty et al first demonstrated that empty nanodiscs composed of a variety of lipids and without embedded membrane proteins can be preserved during nMS [58][59][60][61][62]. Recently, Keener et al [63] discovered that nanodiscs with embedded integral membrane proteins could be preserved and resolved by nMS without the need for ejecting the membrane protein].…”
Section: Use Of Nanodiscs For the Study Of Peripheral Membrane Proteimentioning
confidence: 99%
“…Another challenge is that the mass distribution can become very complex and eventually uninterpretable as different types of lipids and peptide/proteins are added to the nanodisc complex. This challenge can be partially addressed through careful experiment design, and the use of lipids with similar or resonant masses helps simplify the mass distributions [60,61]. In any case, further research will be necessary to establish the limits of the technique.…”
Section: Use Of Nanodiscs For the Study Of Peripheral Membrane Proteimentioning
confidence: 99%
“…However, the peak shape component is not required, and the charge state smooth alone can provide effective deconvolution in well-resolved spectra with the peak width set to 0. Another recent addition to the algorithm included a point smooth, which smoothed the charge state distribution such that neighboring m/z data points had similar charge states by applying a mean filter along each row of the m/z versus charge matrix [7]. The point smooth is applied before the charge/mass smooth, but the order is not critical.…”
Section: Algorithmmentioning
confidence: 99%